Hierarchy of Arthur’s Needs: A Reflection of Psychological and Social Problems in Joker Movie - Indah Saud; Indah Diah Utari Mahajani (LP2M IAIN Sultan Amai Gorontalo, 2022)
The film brings a cultural instrument that educates people. People can see the psychological aspects through the characters and social situation, which influences the characterization in the film. This study examines Joker (2019) a movie containing the psychological conflicts and the society problems of discrimination system in this era which affects much on the character of Arthur who suffers pseudobulbar affect. The researchers used Maslow’s Theory of Human Needs to analyze Arthur’s need to reflect society’s problem needs. A descriptive qualitative method was used in this study because it focused on the human needs of the main character. The primary data was taken from the dialogue in the film, while the secondary data was from articles discussing Arthur Fleck and society as the film's setting. The technique of collecting data was documentation while analyzing data was divided into three stages. First was data reduction; the researcher classified the data of Arthur ‘s needs and explained why they are classified into those categories. The second was data display; the data is structured and presented so that it is easier to be understood. Then, the researchers presented the data into the display categorized on each dialogue that reflected Arthur’s needs levels and the social problems faced by Arthur. Finally, the conclusion was delivered by describing Maslow's data and theory of human needs and elaborating the description of social issues at that era. The result revealed Arthur Fleck had difficulty fulfilling his basic human needs such as physiological, safety, love and belongingness and esteem needs because of the government's broken system and how society treats a person who suffers mental health disorder like Arthur Fleck. The failure to fulfill those needs has made Arthur actualize himself as the cold-blooded clown, The Joker. Then, it helps him to be recognized and being acknowledged by others.